Relationship between Body Mass Index, Age, and Muscular Endurance among Soccer Players in Medan, North Sumatra - Sarah, Dewi Maya; Siregar, Yahwardiah; Eyanoer, Putri Chairani (Indonesian Journal of Medicine, 2019)
Background: Maintaining body mass index is one of the social problems, especially for young athletes. This study aimed to determine the relationship of body mass index (BMI) and age to muscular endurance in soccer athletes in Medan.Subjects and Method: This was a cross-sectional study soccer clubs in Medan, North Sumatera, Indonesia, in April 2018. A sample of 96 soccer players was selected for this study. The dependent variable was muscular endurance. The independent variables were BMI and age. Body weight was measured by weight scale. Body height was measured by microtoise. The other data were collected by questionnaire. Muscle endurance was assessed by 1 minute push up test. The data were analyzed by Person product moment.Results: BMI was positively correlated with muscle endurance but it was not statistically significant (r = 0.09; p = 0.390). Age was positively correlated with muscle endurance and it was statistically significant (r= 0.62; p= 0.001).Conclusion: BMI and age are positively correlated with muscle endurance among soccer players.Keywords: BMI, muscle endurance, soccer athleteCorrespondence: Dewi Maya Sarah. Masters Program in Biomedics, Faculty of Medicine, Universitas Sumatera Utara. Jl. Dokter Mansur, Medan, Sumatera Utara, Indonesia. Email: dewidewimayasarah@ymail.com. Mobile: 081295583909.Indonesian Journal of Medicine, (2019), 4(1): 21-27https://doi.org/10.26911/theijmed.2019.04.01.04